Ko te tikanga mo nga inoi o te ata, : i nga ra katoa o te tau. - Church of England; Church of England; Te perehi o Te Pihopa ([No te Kareti : I taia tenei ki te perehi a Te Pihopa?, 1850)
Lists of daily Bible lessons, morning and evening prayers with the litany, and 42 hymns.
Caption title.
Follows the text of the 1848 prayerbook and printed on thin paper of the type used at the College Press in 1850. The work is securely dated 1850 by the omission from the state prayers of the Queen Dowager Adelaide, who died 4 Dec., 1849.
With: Ko nga upoko mo etahi Ratapu ... EMI 0371 W.206(i) and Ko nga himene. EMI 0370 W.206(iii). [No te Kareti : I taia tenei ki te perehi a Te Pihopa?, 1850].
Williams
Keywords: Church of England -- Prayer-books and devotions -- Maori; Church calendar; Maori language -- Texts; Hymns, Maori